The role of KIBRA in reconstructive episodic memory - Armin Zlomuzica; Friederike Preusser; Susanna Roberts; Marcella L. Woud; Kathryn J. Lester; Ekrem Dere; Thalia C. Eley; Jürgen Margraf (BMC, 2018)
Abstract Background In order to retrieve episodic past events, the missing information needs to be reconstructed using information stored in semantic memory. Failures in these reconstructive processes are expressed as false memories. KIBRA single nucleotide polymorphism (rs17070145) has been linked to episodic memory performance as well as an increased risk of Alzheimer's disease and post-traumatic stress disorder (PTSD). Methods Here, the role of KIBRA rs17070145 polymorphism (male and female CC vs. CT/TT carriers) in reconstructive episodic memory in the Deese-Roediger-McDermott (DRM) paradigm was investigated in N = 219 healthy individuals. Results Female participants outperformed males in the free recall condition. Furthermore, a trend towards a gender x genotype interaction was found for false recognition rates. Female CT/TT carriers exhibited a lower proportion of false recognition rates for associated critical lures as compared to male CT/TT. Additionally, an association between KIBRA rs17070145 genotype, familiarity and recollection based recognition performance was found. In trials with correct recognition of listed items CT/TT carriers showed more "remember", but fewer "know" responses as compared to CC carriers. Discussion and conclusion Our findings suggest that the T-allele of KIBRA rs17070145 supports recollection based episodic memory retrieval and contributes to memory accuracy in a gender dependent manner. Findings are discussed in the context of the specific contribution of KIBRA related SNPs to reconstructive episodic memory and its implications for cognitive and emotional symptoms in dementia and PTSD.